2015
DOI: 10.15421/011510
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and dynamics of amphibians in floodplain ecosystems of the Samara river

Abstract: Надано оцінку впливу чисельності та різноманіття угруповань земноводних на стан лісових екосистем у різних парцелах. Серед досліджених видів земноводних за допомогою факторів ентропії, коефіцієнтів різноманіття встановлено домінантний вид. Урахування впливу предикторів дає можливість виявити чисельність і таксономічне різноманіття амфібій в умовах заплавної липово-ясеневої діброви. У результаті обліку виявлено Pelobates fuscus (Laurenti, 1768), Rana arvalis Nilsson, 1842, Bufo bufo (Linnaeus, 1758), Bombina bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
4
0
2
Order By: Relevance
“…The moisture content in the soil surface layer at the time of the study was 3.58±0.24 %. The bulk density of soil surface layer varied widely (from 0.33 to 1.48 g/cm 3 ). The macroaggregates larger than 10 mm, the proportion of which was 23.46 ± 0.98% (Fig.…”
Section: Figure 3 Spatial Variation Of the Soil Variables Within The Experimental Polygonmentioning
confidence: 99%
See 1 more Smart Citation
“…The moisture content in the soil surface layer at the time of the study was 3.58±0.24 %. The bulk density of soil surface layer varied widely (from 0.33 to 1.48 g/cm 3 ). The macroaggregates larger than 10 mm, the proportion of which was 23.46 ± 0.98% (Fig.…”
Section: Figure 3 Spatial Variation Of the Soil Variables Within The Experimental Polygonmentioning
confidence: 99%
“…These ecosystems occupy a small part of the territory of the steppe zone of Ukraine, but there is a refuge of a large variety of soils, vegetation and animal communities [2]. The environmental processes occurring at landscape levels are directly reflected in the state of the floodplain ecosystems [3]. The small-scale variation of herb-layer community structure is affected by the soil properties, overstorey structural features and factors of the neutral nature.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies of fish have shown that climate change has significant relationships with species range shifts (Chu et al, 2005;Sokolov, & Zhukov, 2014;Sokolov & Zhukov, 2016), recruitment (Ficke et al, 2007, Sokolov & Zhukov, 2017, fecundity (Sundby & Nakken, 2008;Zhukov & Gubanova, 2015a), and abundance (Kallemeyn, 1987;Wingate & Secor, 2008, Zhukov & Gubanova, 2015b, but few have documented climate effects on the timing of spawning in fishes (Bondarev & Zhukov, 2017). The "match-mismatch hypothesis" assumes that the onset and duration of fish spawning and thus the temporal appearance of their larvae are relatively constant each year.…”
Section: Introductionmentioning
confidence: 99%
“…К их числу можно отнести пространственно распределенные факторы среды, которые структурируют сообщества в соответствии с теорией экологической ниши (Hutchinson, 1957(Hutchinson, , 1965. Также важно отметить, что на некоторых пространственных уровнях в структурировании группировок видов играют важную роль межвидовые взаимодействия (Schoener, 1974;Wilson, Habiba, 1995;Belyea, Lancaster, 1999;Zhukov, Gubanova, 2015). Межвидовые взаимодействия могут привести к двум противоположным типам динамики.…”
Section: Introductionunclassified